2014
DOI: 10.1063/1.4878094
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Imaging the effects of the antisymmetric-stretching excitation in the O(3P) + CH4(v3 = 1) reaction

Abstract: Effects of one-quantum excitation of the antisymmetric-stretching mode of CH4(v3 = 1) on the O(3P) + CH4 reaction were studied in a crossed-beam, ion-imaging experiment. In the post-threshold region, we found that (1) the product state distributions are dominated by the CH3(00) + OH(v′ = 1) pair, (2) the product angular distributions extend toward sideways from the backward dominance of the ground-state reaction, and (3) vibrational excitation exerts a positive effect on reactivity, but translational energy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 43 publications
9
39
0
Order By: Relevance
“…[7][8][9][10] In 2014 an experimental study also appeared investigating the effects of the antisymmetric stretching excitation on the angular distributions of the O( 3 P) + CH 4 (v 3 = 0, 1) reactions. 11 The experiment found that the angular distributions are backward scattered for the groundstate reaction and shift toward sideways and forward directions upon stretching excitation. However, a recent theoretical study found very similar backward scattering for both the O + CH 4 (v = 0) and O + CH 4 (v 3 = 1) reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] In 2014 an experimental study also appeared investigating the effects of the antisymmetric stretching excitation on the angular distributions of the O( 3 P) + CH 4 (v 3 = 0, 1) reactions. 11 The experiment found that the angular distributions are backward scattered for the groundstate reaction and shift toward sideways and forward directions upon stretching excitation. However, a recent theoretical study found very similar backward scattering for both the O + CH 4 (v = 0) and O + CH 4 (v 3 = 1) reactions.…”
mentioning
confidence: 99%
“…Furthermore, we report predictions for the symmetric-stretchingexcited O + CH 4 (v 1 = 1) reaction, for which experiment is planned, 11 and provide OH rotational distributions, which can be directly compared to experiment 12 in the case of O + CH 4 (v = 0).…”
mentioning
confidence: 99%
“…In addition to the diverse barrier locations, the barrier heights of the three reactions are also significantly different. The theoretically calculated adiabatic barriers 30 (the experimentally measured thresholds) are 1.03 kcal mol −1 (<0.5 kcal mol −1 ), 31,32 3.4 kcal mol −1 (∼2.5 kcal mol −1 ), 33,34 and 10.1 kcal mol −1 (∼8.0 kcal mol −1 ) 35,36 for the ground state reactions of CHD 3 (v = 0) with F, Cl, and O( 3 P), respectively. [The zero-point-energy corrections have been added to the calculated classical barrier heights 30 for the theoretically adiabatic barriers.]…”
Section: Introductionmentioning
confidence: 90%
“…30,54,55 Again, the ground-state reaction has been extensively investigated and is characterized by a direct abstraction pathway with the rebound mechanism. 35,36,[56][57][58][59][60][61][62][63] This is to be contrasted to the ground-state reaction of F + CHD 3 , for which dual mechanisms partake: a direct abstraction and a resonance-mediated pathway that prevails at lower collision energies. 38,39 Figure 3 illustrates the effects of CH stretch-excitation of CHD 3 (v 1 = 1) on the CD 3 (v = 0) product, which is the dominant product channel.…”
Section: O( 3 P) + Chd 3 (V 1 = 1): a Central Barrier Reactionmentioning
confidence: 99%
See 1 more Smart Citation